BIODOC - the transition from research project to fully fledged service - Bevan, Simon J.; Evans, Janet; Harrington, John; Turner, Emma (UKSG, 1998)
This is the third in a series of papers describing BIODOC, a service now in its fourth year that addresses the access versus holdings debate in a University library. The main aims of the study were to evaluate the cost effectiveness of a wholly access based information service, to analyse user perception/receptivity and the impact of such a service, as well as to improve upon the existing service to the staff and students involved. As part of the project the Library also wished to compare document supplier performance and disseminate all findings among the academic and research communities.